Clinical Usefulness of a Mobile Application for the Appropriate Selection of the Antiarrhythmic Device in Heart Failure. - CURCIO, ANTONIO; DE ROSA, SALVATORE; SABATINO, JOLANDA; DE LUCA, SIMONA; BOCHICCHIO, ANGELA; POLIMENI, ALBERTO; SANTARPIA, GIUSEPPE; RICCI, PIETRANTONIO; INDOLFI, CIRO (Pacing & Clinical Electrophysiology, 2016)
Background Appropriate selection of implantable cardioverter defibrillator (ICD) or cardiac resynchronization therapy (CRT) device can be challenging in patients with left ventricular (LV) dysfunction. In this setting, limited information exists about the role of medical applications in helping physicians to choose the most useful device. Methods We developed a medical application that provides guidelines-based algorithms for helping doctors in decision process using the Apache Cordova application programming interface. e-CRTD App was tested in 36 consecutive patients (age 66.4 ± 8.5 years, 31 males) with diagnosis of heart failure (HF) addressed to electrophysiology laboratory for evaluation of ICD (N = 18) or CRT with defibrillator device (CRT-D; N = 18) implantation. Two separate teams evaluated each patient independently: expert electrophysiologists (Group A); cardiologists in training using the App (Group B). Results The outcomes of the clinical evaluation performed by Groups A and B were similar in 100% of patients in terms of classes of recommendations to device (Class I in eight cases, Class IIa in seven cases, Class III in the remaining 21). Surprisingly, the majority of indications from the general practitioners to cardiac device were inappropriate (N = 17 ICD, and N = 4 CRT-D, Class III); nevertheless, e-CRTD App helped Group B (nonexpert cardiologists) in excluding all these cases. Conclusions This study describes and validates a mobile application realized to help the decision-making process in HF patients candidate to ICD/CRT-D. This application supports physicians to assess the eligibility for ICD or CRT-D according to current guidelines in patients with LV dysfunction.